2012
DOI: 10.1007/s12272-012-1108-5
|View full text |Cite
|
Sign up to set email alerts
|

A new triterpenoid from Alisma orientale and their antibacterial effect

Abstract: A new triterpenoid, named alisol Q 23-acetate, as well as fourteen known terpenes, alisol B 23-acetate (2), alisol B (3), alismol (4), 10-O-methyl-alismoxide (5), alismoxide (6), 11-deoxyalisol C (7), 13β,17β-epoxyalisol B 23-acetate (8), 4β,12-dihydroxyguaian-6,10-diene (9), alisol C 23-acetate (10), alisolide (11), 16β-methoxyalisol B monoacetate (12), alisol A (13), 16β-hydroxyalisol B 23-acetate (14), alisol A 24-acetate (15) were isolated from the rhizomes of Alisma orientale. The structures of compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 12 publications
1
58
0
Order By: Relevance
“…1. Many pharmacological studies have revealed that AB23A has several pharmacological activities, such as antihepatitis virus, anti-proliferative activity of cancer cell lines and antibacterial effects (12)(13)(14). Recently, we have demonstrated that AB23A has promotive effect on liver regeneration and protective effect through FXR activation in mice (15,16).…”
Section: Introductionmentioning
confidence: 98%
“…1. Many pharmacological studies have revealed that AB23A has several pharmacological activities, such as antihepatitis virus, anti-proliferative activity of cancer cell lines and antibacterial effects (12)(13)(14). Recently, we have demonstrated that AB23A has promotive effect on liver regeneration and protective effect through FXR activation in mice (15,16).…”
Section: Introductionmentioning
confidence: 98%
“…Most beneficial effects of AMR are attributed to the presence of protostane terpenoids, which are relatively abundant in this preparation. Previous studies have indicated that triterpenoids have diverse biological activities such as hypolipidemic [1], anti-proliferative activities [6], antibacterial [7], antiplasmodial [8], antioxidative [9] and anti-inflammatory bioactivities [10].…”
Section: Introductionmentioning
confidence: 99%
“…The EtOAc fraction was purified using various column chromatographies to yield twelve guaiane-type sesquiterpenoids (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Resultsmentioning
confidence: 99%